Improving the Quality in Writing Descriptive Texts of Madrasah Aliyah Students Through Directed Writing Activity Strategy - Muhammad Lukman Syafii (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This study was intended to improve the tenth graders’ quality in writing a descriptive text at Madrasah Aliyah through the Directed Writing Activity strategy. Its design was action research consisting of 4 stages, namely planning the action, implementing and observing the action, and reflecting on the action. Its subjects were class X consisting of 31 students. There were 3 instruments used to collect the data needed, i.e. fieldnotes, portfolios, a scoring guide, and questionnaire. The criteria for success of this study were (1) all students participated in the teaching and learning process, (2) all students got score of equal to or more than 3 in each aspect of writing. The findings indicated that in Cycle 1, the study did not meet the criteria of success. Concerning the first criterion, it was only 99% students following the teaching and learning process. One student was absent from the first meeting. In connection with the second criterion, 18 students (58.06%) had achieved a score of equal to or more than 3 and the rest, 13 students (41.94%) got scores below 3. Because the first cycle did not meet the criteria of success, so the researcher carried out the second cycle. All students (100%) participated in the teaching and learning process. In addition to the second criterion, all students got score equal to even greater than 3 in each aspect of writing. From the findings, it can draw the conclusion that the directed writing activity is being able to upgrade the quality in writing descriptive texts of students.